Mycobacterium avium subsp. avium found in raptors exposed to infected domestic fowl - Kriz, Petr; Kaevska, Marija; Bartejsova, Iva; Pavlik, Ivo (Avian diseases, 2013)
We report a case of a falcon breeding facility, where raptors (both diurnal and nocturnal) were raised in contact with domestic fowl (Gallus gallus f. domesticus) infected by Mycobacterium avium subsp. avium. Fecal and environmental samples from 20 raptors and four common ravens (Corvus corax) were collected. Mycobacterium a. avium DNA was detected in feces of four raptors (bald eagle [Haliaeetus leucocephalus], eagle owl [Bubo bubo], barn owl [Tyto alba], and little owl [Athene noctua]) using triplex quantitative real-time PCR. As both the flock of domestic fowl and one of the infected raptors had the same origin (zoological collection), they might have had a common source of colonization/infection. However, the detection of M. a. avium in feces of three other raptors may point at transmission of the agent between the birds in the facility. Contact of raptors with domestic fowl infected by M. a. avium may pose a risk for transmission of the infection for them; however, raptors from the falcon breeding facility seemed to be relatively resistant to the infection.
Keywords: Liver; kur domácí; Animals; Intestines; ptačí tuberkulóza; Female; feces; Feces; játra; Chickens; slezina; Avian Proteins; ženské pohlaví; Poultry Diseases; RNA, Ribosomal, 16S; Strigiformes; RNA ribozomální 16S; nemoci drůbeže; Mycobacterium avium; Eagles; Crows; střeva; vrány; ptačí proteiny; Czech Republic; Tuberculosis, Avian; Spleen; Česká republika; Accipitridae; zvířata; Stringiformes; kvantitativní polymerázová řetězová reakce; Real-Time Polymerase Chain Reaction